Can you count in the dark? Turn off the light and find out! - Ingle, Annie; Brunkus, Denise (New York Random House, 1993)
As a boy roams around his house and yard, illustraations and rhyming present various items from one moom to ten stars. Parts of the puctures are only visible when the lights are out.
2/2006, purchased
Keywords: Counting -- Juvenile literature; Glow-in-the-dark books -- Specimens